2021
DOI: 10.1021/acsenergylett.1c00283
|View full text |Cite
|
Sign up to set email alerts
|

Iridium Oxide Modified with Silver Single Atom for Boosting Oxygen Evolution Reaction in Acidic Media

Abstract: Electrocatalytic oxygen evolution in acidic media is crucial for promoting water splitting. Herein, we report an Ag 1 /IrO x single atom catalyst (SAC) with Ag single atoms embedded in an IrO 2 matrix obtained through the oxidation of IrAg single atom alloy (SAA). The Ag 1 /IrO x SAC delivers a low overpotential of 224 mV at current density of 10 mA cm −2 and a long-term durability better than that of commercial Ir (C-Ir). DFT calculation indicates that six Ir atoms neighboring the single Ag atom exhibit a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…The current catalyst of choice on the anode uses Ir and its oxide with a typical loading of a few milligrams per square centimeter . Limited by the scarcity, high cost, and low annual production of PGMs, studies have focused on reducing PGM loadings or developing novel electrocatalysts with PGM-free metals, while maintaining competitive performance. In addition to catalyst development, advanced manufacturing methods to obtain novel structured catalyst nanoparticles are also critical to boosting electrode cost competitiveness. …”
Section: Introductionmentioning
confidence: 99%
“…The current catalyst of choice on the anode uses Ir and its oxide with a typical loading of a few milligrams per square centimeter . Limited by the scarcity, high cost, and low annual production of PGMs, studies have focused on reducing PGM loadings or developing novel electrocatalysts with PGM-free metals, while maintaining competitive performance. In addition to catalyst development, advanced manufacturing methods to obtain novel structured catalyst nanoparticles are also critical to boosting electrode cost competitiveness. …”
Section: Introductionmentioning
confidence: 99%
“…4,5 The introduction of high-performance electrocatalysts plays an important role in accelerating their reaction kinetics, improving electron transfer efficiency, and reducing energy consumption for the HER and OER. 6–8 Currently, the highly active electrocatalysts of the HER and OER are noble metal-based catalysts such as Pt, RuO 2 and IrO 2 due to their low overpotentials and high electrical conductivity. 9–11 However, their low reserves and high cost greatly limit their widespread commercial application.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Camila et al 12 had done quantitative benchmarking work on IrO x to deduce a selection of suitable catalysts for diminishing the cost of PEM; Marion et al 13 based on amorphous IrO x revealed that surface structural features have a greater effect on OER activity than the iridium oxidation state. In the design of low iridium and high activity catalysts; Liu et al 14 reported an Ag 1 /IrO x single atom catalyst through the oxidation of an IrAg single atom alloy, which can deliver a low overpotential of 224 mV at a current density of 10 mA cm À2 and better durability; besides, Hutchings et al 15 designed layered IrO x -Ni (OH) x which had a a Key Laboratory of Agro-Forestry Environmental Processes and Ecological low Ir content without impairing the catalytic activity or stability. There are also many new discoveries, such as La-IrO x amorphous solid solution with an open structure, 16 La and Pt modified with ultra-small IrO 2 nanoparticles, 17 ultrafine IrRu nanoclusters supported on amorphous tellurium, 18 high-index facets of Ir modified by Pd, 19 hafnium-modified iridium oxide, 20 etc.…”
Section: Introductionmentioning
confidence: 99%